PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI ADMINISTRASI PENJUALAN DAN PEMBELIAN PADA TOKO SEJAHTERA - -, arnold -; Santoso, Leo Willyanto; Adipranata, Rudy (Jurnal Infra, 2014)
Sejahtera stores have difficulty in dealing with the administration because its operation is still manual, i.e. the sale and purchase transactions, preparing reports and other expenditures problems. Thus allow for errors in the calculation of the invoice and the risk of losing documents. It can be harmful if done every day.To resolve the problems then a new system was designed and implemented. The new system was designed using Data Flow Diagrams (DFD) and Entity Relationship Diagram (ERD) using Microsoft Visio and Power Designer, and implemented using Microsoft SQL Server 2012. The system includes the purchase is process, process of sale transaction, process of making an income statement, making the card stock.The system was created to facilitate the Sejahtera Stores to solve existing problems and to assist in the administration of Sejahtera Store.